Herman Sherman Bassett papers, - Bassett, Herman S., 1869-1965
Biographical material on the life of Herman Sherman Bassett collected by E. T. Becher. Includes a "Pioneer Interview with Herman Sherman Bassett" done by Becher (handwritten and typewritten notes), and a typewritten manuscript entitled "H. S. Bassett Recalls Stories Of Territorial Days For Liberty Grange." Also present is a manuscript entitled "Information as Written to Me" by Bertha Bassett Shissler (1953) and correspondence with Bassett's daughter, Florence Bassett. There is also a "Bassett Family Record" done by Becher.